STRATEGI PENGINJILAN DILINGKUNGAN KAUM WARIA KAMPUNG BANDAN JAKARTA - Rikardo P. Sianipar; Imam Teguh Setiawan (STT Bethel The Way, 2020)
This researh reviews the evangelistic strategies of transvestites in the Jakarta bandan village, who are entitled to the way of salvation through the gospel. Judging from the number of transvestites who do not understand the direction and purpose of escaping, a biblical evangelistic strategy can lead them to repentance that is truly and pleasing to their original nature as men. The form of research carried out is qualitative with methods of observation, literature and interviews with sources in the Jakarta Bandan village area. Resource persons, discuss that they have not been able to solve the lives of transvestites. Researchers see very significant results to restore the lives of transvestites through biblical evangelistic strategies. A change of life and a smarter mindset for the personal awakening of transvestites. Researchers concluded, evangelism is a request that must be done for every person who believes in the word of God. Of course, by applying biblical evangelism, one must go through competent education, training and learning. It seems to be big enough so that transvestites from the Jakarta bandan village can do the word of God that they have received.